PENDAMPINGAN PENGEMBANGAN KAPASITAS PRODUKSI DENGAN VALUE CHAIN ANALYSIS PADA UMKM BATIK SEKARNITI YOGYAKARTA - Kholifah Fil Ardhi; Fitri Amaliyah; Naila Hanum (Jurnal Abdimas Sangkabira, 2021)
MSME activities (Micro, Small and Medium Enterprises) are dominated by human labor or labor-intensive, which means that the absorption of labor is very high in the MSME sector. Batik Sekarniti is a small industry engaged in the production of traditional batik. PKM activities carried out online and offline went well and smoothly. The face-to-face meeting aims to conduct a pre-survey of the condition of MSMEs so as to help plan PKM activities. The core of the activity is mentoring and training which is held online using Google Meet media. The participants of the activity were 30 people consisting of two owners and 28 employees of the Batik Sekarniti UMKM located in Temanggal, Wijimulyo, Nanggulan, Kulon Progo, DI. Yogyakarta. The results of the activity show that there is potential for UMKM Batik Sekarniti to increase production capacity, namely in the process of batik writing.